The English Teachers’ and Students’ Perception on the Differentiated Instruction - Mutiara Ningsih Kurnia Dewi1; -, Tri Mulyati; Wageyono (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
Typically, teachers are expected to meet the diverse needs of students in the classroom through appropriate teaching strategies. Differentiated instruction (DI) is one such approach that aims to address students' diverse readiness levels, interests and learning profiles. However, the implementation of DI can be affected by how teachers and students perceive its implementation. The objectives of this study was to describe the English teachers’ perceptions and the students’ perception on the differentiated instruction. The research method was descriptive quantitative. The researcher used a questionnaire in collecting data. The respondents of this research were three English teachers and seventeen eleventh-grade students at SMA Negeri 1 Banyuwangi. The researcher analyzed the data of questionnaires by using statistical analysis with this formula: P = n/N x 100%. The results of the study showed that the English teachers had a positive perception on the differentiated instruction. The result was 77,8%. The students also perceived differentiated instruction positively. It was 74,5%. Content and process differentiation received favorable ratings from both teachers and students. The findings suggest that differentiated instruction effectively supports student engagement and personalized learning. Future studies are recommended to include qualitative data to gain deeper insight into the students’ enggament and other factors affecting the teaching and learning process.